2021
DOI: 10.5937/aneksub2146115a
|View full text |Cite
|
Sign up to set email alerts
|

Are digital financial payments constrained by the country's income: Evidence from the Global Findex database

Abstract: The combined effect of ICT improvement, digitalization and change in clients' habits lead to changes in the financial sector worldwide. Increased use of digital financial services (DFS) is a change that might help to increase financial inclusion, which is particularly important for developing countries. As income is considered a critical driver of digital payments, this study aims to determine whether there is a linear relationship between a country's income measured by the level of Gross National Income per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…The authors found a moderately strong relationship between making a digital in-store merchant payment using a mobile phone and the level of development. These findings are in line with prior studies [6][7][8][9][10][11][12][13][14][15], and support the critical role that income, i.e., country development, plays in determining the use of digital banking services by citizens, and vice versa.…”
Section: Resultssupporting
confidence: 91%
“…The authors found a moderately strong relationship between making a digital in-store merchant payment using a mobile phone and the level of development. These findings are in line with prior studies [6][7][8][9][10][11][12][13][14][15], and support the critical role that income, i.e., country development, plays in determining the use of digital banking services by citizens, and vice versa.…”
Section: Resultssupporting
confidence: 91%